2020
DOI: 10.1021/acsenergylett.0c01387
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Mediated Selectivity Switching of Electrochemical CO2 Reduction from Formate to CO on Carbon Supported Sn

Abstract: Decades of electrochemical CO2 reduction research have led to established rules about the product selectivity, i.e., bare tin yields formic acid as the main product. Here, we present Sn nanoparticles supported on carbon nanotubes (CNTs) in a hollow fiber (Sn-CHF), which produce CO with 10 times higher selectivity than formate. Density functional theory calculations reveal that a strong interfacial field induced by the carbon support enhances the rate-limiting CO2 adsorption and thus CO production on Sn nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 50 publications
3
52
0
Order By: Relevance
“…Additionally, we can confirm that Sn 4+ is not the active site of the CO 2 reduction reaction. This corresponds to previously published data, for example, Lee et al [38] showed that, under neutral conditions, metallic Sn is most likely the active site of CO 2 RR. On the other hand, some authors have found that the Sn electrode possesses an oxide layer and shows excellent catalytic activity for CO 2 reduction, and that the Sn electrode removed its oxide layer, resulting in poor catalytic activity for CO 2 reduction, but with the hydrogen evolution reaction accelerating [23].…”
Section: Resultssupporting
confidence: 92%
“…Additionally, we can confirm that Sn 4+ is not the active site of the CO 2 reduction reaction. This corresponds to previously published data, for example, Lee et al [38] showed that, under neutral conditions, metallic Sn is most likely the active site of CO 2 RR. On the other hand, some authors have found that the Sn electrode possesses an oxide layer and shows excellent catalytic activity for CO 2 reduction, and that the Sn electrode removed its oxide layer, resulting in poor catalytic activity for CO 2 reduction, but with the hydrogen evolution reaction accelerating [23].…”
Section: Resultssupporting
confidence: 92%
“…With an aim to replace Au‐ and Ag‐based high‐cost materials, considerable research efforts have been focused on developing various electrocatalysts based on earth‐abundant elements. These include monometallic Cu atomic nanosheets [ 18 ] and pairs, [ 19 ] Sn nanoparticles, [ 20 ] Zn nanosheets, [ 21,22 ] bimetallic alloys of Cu with Al, [ 23 ] In [ 24 ] and Sn, [ 25–28 ] metal oxides, [ 29,30 ] and chalcogenides, [ 31,32 ] as well as single‐atom Mn, Fe, Co, and Ni carbonitrides [ 33–38 ] and organometallic complexes. [ 39,40 ] Nevertheless, most of them still require high overpotentials to deliver desirable current densities due to their modest activity toward the reduction of chemically inert CO 2 molecule.…”
Section: Introductionmentioning
confidence: 99%
“…This material with encapsulated Ni nanoparticles and abundant doped nitrogen atoms leads to a great improvement in the catalytic activity to produce CO (FE equal to 97.7% at −0.7 V vs. RHE). Lee and co-workers [203] studied the effect of the interfacial field in the CO 2 reduction reaction environment using Sn nanoparticles supported on entangled carbon nanotubes. Interfacial field modulation is a recent strategy that can have a significant impact on catalyst selectivity.…”
Section: Metal Nanoparticles Supported On Carbon-based Materials (M-nps-c)mentioning
confidence: 99%